Generating multi-wing hidden attractors with only stable node-foci via non-autonomous approach. (1st October 2021) - Yang, Yan; Huang, Lilian; Xiang, Jianhong; Bao, Han; Li, Houzhen
Abstract: Hidden attractor is associated with the multistability phenomenon, which has important application prospects in security communication. Recently, the study of multi-wing hidden chaotic attractor with only stable equilibria is a particular interest. By modifying simple 3D quadratic systems, this paper first proposes two systems with two symmetric equilibria. In particular, in a wide parameter region, the two systems have stable node-foci but can generate structural stable double-wing chaotic attractors, which belongs to the category of hidden attractor. The rotation matrix is applied to implement the attractor rotation. In combination with multi-level pulse sequences, multi-wing chaotic attractors with switchable stable node-foci are generated. The multi-wing hidden attractors are experimentally validated by microcontroller-based hardware experiments.